Future Prospect of Gamification-Based Mobile in Physics Learning - Amiruddin, Mohd Zaidi Bin; Nisa', Widyana Zuhrotun; Rahman, Sitti Maizatul Iqma Binti; Saini , Nur Aida Maryani Binti (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
The development of gamification in the world of education today continues to grow. This study aims to find trends, distributions, contributions, and effects of gamification research in various sectors, especially in education, in the last ten years. The Research uses quantitative Research in the form of bibliometric analysis using the Scopus database with the help of visualization from VOSViewer. The results of this analysis show that in 2012-2021 (the last ten years), gamification increased yearly. In addition, the distribution and contribution of gamification are very beneficial for the world of education, with the note that it must be prepared carefully to produce positive outputs. For further Research, it is expected to continue to develop the field of gamification-based mobile in physics learning so that it can be an alternative to various educational levels included in physics learning.